Nutritional and management practices for improved sow productivity and progeny performance - Jenkins, Abigail Karren (My University, 2025)
A total of 7 experiments structured in 6 chapters were performed to investigate the effects of yeast probiotics in lactation and a pre/probiotic combination in nursery diets, evaluate the impact of increased histidine in lactation diets, assess increased standardized ileal digestible lysine levels through additional soybean meal in late gestation, examine allotment strategies in the nursery, assess calcium administration protocols around farrowing, and determine the optimal litter size in relation to functional teat count during lactation. Chapter 1 utilized 720 pigs to evaluate three allotment strategies aimed at assessing variation and determining replications required to detect statistical significance in nursery pig research. Overall, allotting pigs to pens using a bodyweight (BW) grouping strategy resulted in the least within-pen and pen-to-pen variation. The BW grouping method required the fewest pens to detect statistically significant differences. Chapter 2 utilized 28 mixed-parity sows and their offspring to evaluate live yeast supplementation during lactation with or without a pre/probiotic combination during the nursery period on lactation performance, lifetime growth performance, and immune response. The effects of combining a yeast probiotic in lactation diets and a pre/probiotic in nursery diets were not additive. However, feeding a live yeast probiotic during lactation resulted in increased progeny final BW and hot carcass weight. Chapter 3 utilized 87 mixed-parity sows and their offspring to evaluate the effects of increasing standardized ileal digestible (SID) lysine in late gestation diets on lactating sow and litter performance. Increased SID lysine through additional soybean resulted in increased late gestation sow weight gain and piglet average daily gain (ADG) during early lactation. However, litter ADG during late lactation and overall lactation was maximized in litters from sows fed 15.8 g/d of SID lysine. Chapter 4 utilized a total of 88 mixed-parity sows and their litters to evaluate the effects of increasing SID histidine:lysine ratio on sow and litter performance. Overall, sows fed diets with an SID histidine:lysine ratio of 50% had heavier litters on day 7 of lactation and at weaning and greater calculated average daily milk yield. Chapter 5 utilized 1,005 mixed-parity sows and their litters to evaluate the effect of initial litter size relative to functional teat count on sow and litter performance. Overall, sows with 1 less pig than functional teats after cross-fostering had the lowest pig mortality and sow BW loss and greatest pig weaning weight. However, for the greatest number of pigs weaned per litter and pigs weaned per sow per year, 2 more pigs than functional teats after cross-fostering was ideal. Chapter 6 utilized 933 mixed-parity sows and their litters to evaluate calcium administration protocols around farrowing on sow performance. In the overall population, topdressing calcium chloride before farrowing or injecting calcium gluconate peripartum altered sow metabolites but did not influence farrowing performance. However, when comparing at-risk sows among the 3 treatments, administration of calcium gluconate decreased stillbirths and increased percentage of pigs born alive.
Keywords: Sow productivity; Progeny performance; Litter size; Functional teat count; Stillbirths; Sow milk yield